Scalability of the Wireless Sensor Networks on Hierarchical Routing - C M, Ramya; R J, Thejas; B K, Vikas; K M, Vinutha; Appaji, Impana (IJRDO -Journal of Computer Science Engineering, 2017)
A wireless sensor network is the network consisting of numerous small sensor nodes with sensing, processing and wireless communication capabilities. Many routing protocols are suggested for wireless sensor networks due to the several limited resources of a sensor node such as its limited CPU, memory size, and battery. They can be divided into flat and hierarchical routing protocols. The hierarchical routing protocol uses the clustering scheme and shows better performance than flat routing protocols. However, there is an assumption that sensor nodes can communicate with the base station by a one-hop routing in the hierarchical routing protocol. However, if the network size become larger, the hierarchical routing protocol is unsuitable because a long distance between a clusterhead and the base station can cause some communication problems. In this paper, we propose the clusterhead chaining scheme to solve this problem. Our scheme is suitable for vast wireless sensor networks and it was found from the simulation result that the proposed scheme shows better performance than the general hierarchical routing protocol